Pengaruh Konseling Kelompok dengan Art Therapy dalam Mereduksi Loneliness Siswa - Masna Ayu Lumban Toruan; Tri Umari; Munawir Munawir (Ulul Albab: Majalah Universitas Muhammadiyah Mataram, 2026)
This study aimed to analyze the effect of group counseling services employing art therapy techniques in reducing students’ loneliness at SMPN Pekanbaru. The study employed a quantitative approach using a one-group pretest-posttest experimental design. The research subjects consisted of 8 students selected through purposive sampling techniques based on moderate and high levels of loneliness. The research instrument utilized was the UCLA Loneliness Scale Version 3. Data analysis was conducted using the Wilcoxon Signed Rank Test and N-Gain test. The findings revealed a decrease in students’ levels of loneliness after the implementation of group counseling services with art therapy techniques. The results of the Wilcoxon test obtained an Asymp. Sig. (2-tailed) value of 0.030 < 0.05, indicating that group counseling services with art therapy techniques had a significant effect on reducing students’ loneliness. Therefore, group counseling services employing art therapy techniques are considered effective in helping reduce students’ loneliness at SMPN 1 Pekanbaru